Thyroglossal duct cyst coexisting with a fistulous tract: A rare case report and literature review - Ramin Salimnejad; Arash Hasirbaf Momtaz; Ziba Ghoreishi; Majid Shokoohi; Daniyal Bolandhemmat; Mohammad Amin Dolatkhah; Hamed Shoorei; Seyyed Mostafa Ghavami (Elsevier, 2018)
An 11-year-old boy was admitted to the hospital complaining of odorous discharge from an opening in the anterior region of the left side of his neck. During physical examinations, we understood that his cyst moved with deglutition and protrusion of the tongue. In order to get a correct diagnosis of the patient problem, fistulography with contrast agent meglumine was done from the patient neck in two projections, anterior-posterior and anterior-posterior-oblique. By information obtained of physical examinations and his neck radiographs, thyroglossal duct cyst coexisting with a fistulous tract was diagnosed. In adolescents and adults, thyroglossal duct cyst is one the most common causes of midline congenital cyst formation in the neck that may appear anywhere between the base of the tongue and the suprasternal region. Thyroglossal duct cyst develops from a persistence of any portion of the thyroglossal tract in the embryonic period. After birthday, infection of cyst can sometimes lead to fistula formation in the neck. Both of them, thyroglossal duct cyst and thyroglossal fistula, are usually diagnosed by imaging techniques. Keywords: Thyroglossal duct cyst, Thyroglossal fistula, Fistulography